Farmers’ Adoption Level of the Pratapdhan Breed in Backyard Poultry Farming in Udaipur District, Rajasthan, India - Meenu; Ananda K R; Vikash Kumar Meena; Preeti Y H; Ankit Pal (Archives of Current Research International, 2025)
Poultry farming is critical for the development of the economy. It usually has better returns than other livestock activities in developing countries. A study was done to assess the adoption of backyard poultry among 120 farmers in the Udaipur district of Rajasthan, concentrating on the Pratapdhan under AICRP. the study found that most farmers (64.17%) adopted practices to a medium level, with high (19.17%) and low (16.67%) adoption levels following. Adoption was highest in the practices of feeding and watering (96.92%), breeding (85.00%), housing (84.17%), and health care (70.42%). In general, adoption was at a medium level without considerable difference in Girwa and Gogunda tehsils (Z = 0.427, p < 0.01). From the results, it was found that a moderate level of adoption can be improved with further training, extension, and veterinary services. Market linkage building will aid in rural development through income diversification, transforming subsistence poultry farming into a commercial activity.